¬The Development of Student Collaboration Competency in Learning National Defense Path of the Vietnamese Communist Party - Thanh Nghia, Duong; Hoai, Vu Thi Thu (VNU Journal of Science: Education Research, 2023)
Cooperation competency is not only one of the many vital capabilities for people living in the modern day society, but also assists the formulation of an energetic, creative, communicative and adaptive personality. There has been ample evidence on the fact that studying with continuous cooperative work can promote the growth of working skills, which in turn creates opportunities for mutual learning and the discovery of personal abilities. Furthermore, cooperation also helps enhance the sense of responsibility, autonomy and social activeness. Through group work, people can take advantage of their strength in numbers to resolve complicated matters and achieve significant results. This proves the essential role of cooperation competency in creating an all-round personality and developing such traits in the contemporary society - this is the basis for academic achievement. This article defines the framework of students’ cooperation competency in learning National Defense and Security (NDS), investigates the ongoing situation of teaching National Defense Path of the Vietnamese Communist Party (VCP) and suggests several solutions to further boost this characteristic while studying these subjects in accordance with current requirements on reforming the education system of Vietnam.